Confinement and Polarity Effects on the Peptide Packing Density on Mesoporous Silica Nanoparticles - Beitzinger, Bastian (Langmuir : the ACS journal of surfaces and colloids, 2024)
The adsorption of cationic peptide JM21 onto different mesoporous silica nanoparticles (MSNs) from an aqueous solution was studied as a function of pH. In agreement with the literature, the highest loading degrees could be achieved at pH close to the isoelectric point of the peptide where the peptide-peptide repulsion is minimum. However, mesopore size, mesopore geometry, and surface polarity all had an influence on the peptide adsorption in terms of both affinity and maximum loading at a given pH. This adsorption behavior could largely be explained by a combination of pH-dependent electrostatic interactions and confinement effects. It is demonstrated that hydrophobic interactions enhance the degree of peptide adsorption under pH conditions where the electrostatic attraction was absent in the case of mesoporous organosilica nanoparticles (MONs). The lower surface concentration of silanol groups for MON led to a lower level of peptide adsorption under optimum pH conditions compared to all-silica particles. Finally, the study confirmed the protective role of MSNs in preserving the biological activity of JM#21 against enzymatic degradation, even for large-pore MSNs, emphasizing their potential as nanocarriers for therapeutic peptides. By integrating experimental findings with theoretical modeling, this research elucidates the complex interplay of factors that influence peptide-silica interactions, providing vital insights for optimizing peptide loading and stabilization in biomedical applications